The Aging Muscle in Experimental Bed Rest: A Systematic Review and Meta-Analysis - Di Girolamo, Filippo Giorgio; Fiotti, Nicola; Milanović, Zoran; Situlin, Roberta; Mearelli, Filippo; Vinci, Pierandrea; Šimunič, Boštjan; Pišot, Rado; Narici, Marco; Biolo, Gianni (Frontiers in Nutrition, 2021)
Background: Maintaining skeletal muscle mass and function in aging is crucial for preserving the quality of life and health. An experimental bed rest (BR) protocol is a suitable model to explore muscle decline on aging during inactivity. Objective: The purpose of this systematic review and meta-analysis was, therefore, to carry out an up-to-date evaluation of bed rest, with a specific focus on the magnitude of effects on muscle mass, strength, power, and functional capacity changes as well as the mechanisms, molecules, and pathways involved in muscle decay. Design: This was a systematic review and meta-analysis study. Data sources: We used PubMed, Medline; Web of Science, Google Scholar, and the Cochrane library, all of which were searched prior to April 23, 2020. A manual search was performed to cover bed rest experimental protocols using the following key terms, either singly or in combination: “Elderly Bed rest,” “Older Bed rest,” “Old Bed rest,” “Aging Bed rest,” “Aging Bed rest,” “Bed-rest,” and “Bedrest”. Eligibility criteria for selecting studies: The inclusion criteria were divided into four sections: type of study, participants, interventions, and outcome measures. The primary outcome measures were: body mass index, fat mass, fat-free mass, leg lean mass, cross-sectional area, knee extension power, cytokine pattern, IGF signaling biomarkers, FOXO signaling biomarkers, mitochondrial modulation biomarkers, and muscle protein kinetics biomarkers. Results: A total of 25 studies were included in the qualitative synthesis, while 17 of them were included in the meta-analysis. In total, 118 healthy elderly volunteers underwent 5-, 7-, 10-, or 14-days of BR and provided a brief sketch on the possible mechanisms involved. In the very early phase of BR, important changes occurred in the skeletal muscle, with significant loss of performance associated with a lesser grade reduction of the total body and muscle mass. Meta-analysis of the effect of bed rest on total body mass was determined to be small but statistically significant (ES = −0.45, 95% CI: −0.72 to −0.19, P < 0.001). Moderate, statistically significant effects were observed for total lean body mass (ES = −0.67, 95% CI: −0.95 to −0.40, P < 0.001) after bed rest intervention. Overall, total lean body mass was decreased by 1.5 kg, while there was no relationship between bed rest duration and outcomes (Z = 0.423, p = 672). The meta-analyzed effect showed that bed rest produced large, statistically significant, effects (ES = −1.06, 95% CI: −1.37 to −0.75, P < 0.001) in terms of the knee extension power. Knee extension power was decreased by 14.65 N/s. In contrast, to other measures, meta-regression showed a significant relationship between bed rest duration and knee extension power (Z = 4.219, p < 0.001). Moderate, statistically significant, effects were observed after bed rest intervention for leg muscle mass in both old (ES = −0.68, 95% CI: −0.96 to −0.40, P < 0.001) and young (ES = −0.51, 95% CI: −0.80 to −0.22, P < 0.001) adults. However, the magnitude of change was higher in older (MD = −0.86 kg) compared to younger (MD = −0.24 kg) adults. Conclusion: Experimental BR is a suitable model to explore the detrimental effects of inactivity in young adults, old adults, and hospitalized people. Changes in muscle mass and function are the two most investigated variables, and they allow for a consistent trend in the BR-induced changes. Mechanisms underlying the greater loss of muscle mass and function in aging, following inactivity, need to be thoroughly investigated.